Pharmacological effects of Eleutherococcus senticosus on the neurological disorders. (17th July 2022) - Li, Xi‐Tao; Zhou, Jie‐Chun; Zhou, Yu; Ren, Ying‐Shan; Huang, Yu‐Hong; Wang, Shu‐Mei; Tan, Long; Yang, Zhi‐You; Ge, Yue‐Wei
Abstract: Eleutherococcus senticosus is a medicinal plant widely used in traditional medicine and edible remedies with effects on anti‐fatigue, sleep improvement, and memory enhancement. Recently, the application of E. senticosus to neurological disorders has been a focus. However, its overall pharmacological effect on neural diseases and relevant mechanisms are needed in an in‐depth summary. In this review, the traditional uses and the therapeutic effect of E. senticosus on the treatment of fatigue, depression, Alzheimer's disease, Parkinson's disease, and cerebral ischemia were summarized. In addition, the underlying mechanisms involved in the anti‐oxidative damage, anti‐inflammation, neurotransmitter modulation, improvement of neuronal growth, and anti‐apoptosis were discussed. This review will accelerate the understanding of the neuroprotective effects brought from the E. senticosus, and impetus its development as a phytotherapy agent against neurological disorders.